2009
DOI: 10.2353/ajpath.2009.090019
|View full text |Cite
|
Sign up to set email alerts
|

MYCN Promotes the Expansion of Phox2B-Positive Neuronal Progenitors to Drive Neuroblastoma Development

Abstract: Amplification of the oncogene MYCN is a tumorigenic event in the development of a subset of neuroblastomas that commonly consist of undifferentiated or poorly differentiated neuroblasts with unfavorable clinical outcome. The cellular origin of these neuroblasts is unknown. Additionally, the cellular functions and target cells of MYCN in neuroblastoma development remain undefined. Here we examine the cell types that drive neuroblastoma development in TH-MYCN transgenic mice, an animal model of the human disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 48 publications
5
82
0
Order By: Relevance
“…Neuroblasts in hyperplasia lesions strongly expressed the transgene MYCN and the proliferation marker Ki-67 and were negative for the differentiation marker tyrosine hydroxylase (Fig. 1E), as previously reported (20,42). Taken together, these results showed that midkine was highly expressed in precancerous hyper-proliferative cells.…”
Section: Resultssupporting
confidence: 75%
“…Neuroblasts in hyperplasia lesions strongly expressed the transgene MYCN and the proliferation marker Ki-67 and were negative for the differentiation marker tyrosine hydroxylase (Fig. 1E), as previously reported (20,42). Taken together, these results showed that midkine was highly expressed in precancerous hyper-proliferative cells.…”
Section: Resultssupporting
confidence: 75%
“…Neuroblastoma is uniformly p53 wild type, and p53 signaling can be robustly stimulated in vitro and in vivo in these cancers (25,46). These multiple effects of MYCN may manifest themselves at distinct time points of tumorigenesis (3,47). Hence MYCN function may help to prevent differentiation and apoptosis of neuroblast precursors during tumor initiation, and then later restrain proliferation through p53-dependent and -independent mechanisms to match local nutrient and oxygen supplies within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…MYCN is sufficient to elicit NB development, but in MYCN mouse NB models, neuroblast proliferation and sympathetic ganglion size are not increased during embryonic and early postnatal development (Hansford et al, 2004;Alam et al, 2009;Althoff et al, 2015). To address the in vivo effects of MYCN overexpression in chick sympathetic neuroblasts, we electroporated neural crest cells in 2-d-old (E2) chick embryos with Pbflanked CAGGS-GFP, CAGGS-MYCN, and Pb plasmid and analyzed E5 embryos for the proportion of proliferating EdU ϩ / TH ϩ /GFP ϩ neuroblasts.…”
Section: Mycn Overexpression Increases Neuroblast Proliferation In Vivomentioning
confidence: 99%
“…In embryonic sympathetic ganglia of both TH-MYCN and wild-type mice clusters of highly proliferating cells are present but selectively maintained postnatally in TH-MYCN ganglia (Hansford et al, 2004;Alam et al, 2009). In the Ki-Alk mouse, neuroblast proliferation is transiently increased in embryonic and early postnatal ganglia but terminated at postnatal day 18 (Cazes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%